HPV-independent Precursors Mimicking High-grade Squamous Intraepithelial Lesions (HSIL) of the Vulva. (November 2020) - Rakislova, Natalia; Alemany, Laia; Clavero, Omar; del Pino, Marta; Saco, Adela; Marimon, Lorena; Quirós, Beatriz; Lloveras, Belen; Ribera-Cortada, Inmaculada; Alejo, Maria; Pawlita, Michael; Quint, Wim; et al.
Abstract : Two etiopathogenic types of vulvar squamous cell carcinoma (VSCC) have been described: human papillomavirus (HPV)-associated and HPV-independent. Precursor lesions, frequently identified in the adjacent skin, are also distinct in the 2 types of VSCC: high-grade squamous intraepithelial lesions (HSILs) in HPV-associated VSCC and differentiated vulvar intraepithelial neoplasia (dVIN) or vulvar acanthosis with altered differentiation in HPV-independent VSCC. Although HPV-independent precursors mimicking HSIL have been described in the vulva, their frequency and morphologic spectrum have not been completely characterized. We explored, in a large series of HPV-independent VSSC, the frequency and the histologic features of precursors mimicking HSIL. We included 779 DNA HPV-negative/p16-negative VSCC with at least 1 cm of adjacent skin. We evaluated the histologic and immunohistochemical (p16 and p53) characteristics of the intraepithelial lesions, focusing on precursors mimicking HPV-associated vulvar HSIL. A total of 254 tumors (33%) had adjacent premalignant lesions. Of them, 186 (73%) had dVIN, 22 (9%) had vulvar acanthosis with altered differentiation, and 46 (18%) had lesions that mimicked HSIL. The mean age of the patients with these HSIL-like lesions was 72±15 years. Twenty-six of these HSIL-like lesions had basaloid morphology, 13 warty, and 7 mixed basaloid/warty features. All the HSIL-like precursors were DNA HPV-negative/p16-negative; 74% of them showed p53 abnormal staining and 35% of them had areas of conventional dVIN. In conclusion, about one fifth of the HPV-independent precursors mimic HSIL, showing either basaloid or warty features. Older age and the presence of areas of typical HPV-independent intraepithelial lesions, together with p16 negativity, should raise suspicion of an HPV-independent etiology.